ASUHAN KEPERAWATAN PADA BAYI RESPIRATORY DISTRESS SYNDROME DENGAN PEMBERIAN PRONE POSITION DI RUANG PERINATOLOGI RS AN-NISA TANGERANG NURSING CARE FOR BABIES WITH RESPIRATORY DISTRESS SYNDROME BY PROVIDING PRONE POSITION IN THE PERINATALOGY ROOM OF AN-N - Rusmiyati, Rosy; Ria Setia Sari; Siti Muthoharoh (Cahaya Ilmu Bangsa Institute, 2024)
ABSTRAK Latar Belakang: Respiratory Distress Syndrome merupakan salah satu penyebab kematian neonatus yang paling ditemukan, penyakit ini membunuh sekitar 40.000 neonatus setiap tahun di Amerika Serikat. Sindrom gangguan pernapasan Respiratory Distress Syndrome diketahui disebabkan oleh defisiensi surfaktan primer dan tekanan saluran napas positif.. Tujuan: Karya Tulis Ilmiah ini bertujuan untuk memberikan asuhan keperawatan pada bayi dengan Respiratory Distress Syndrome dengan intervensi inovasi prone position terhadap status oksigenasi di ruang perinatalogi Rs An-Nisa Tangerang. Metode: pemberian asuhan keperawatan pada bayi dengan Respiratory Distress Syndrome dengan intervensi inovasi proe position terhadap status oksigenasi. Hasil: Berdasarkan Studi kasus pada pasien kelolaan diperoleh hasil dari intervensi yang telah dilakukan bahwa adanya pengaruh pemberian pronasi terhadap perbaikan oksigenasi pada bayi dengan Respiratory Distress Syndrome (RDS). Kata Kunci: Respiratory Distress Syndrome, Prone Position ABSTRAC Background: Respiratory Distress Syndrome is one of the most common causes of neonatal death, this disease kills approximately 40,000 neonates every year in the United States. Respiratory distress syndrome Respiratory Distress Syndrome is known to be caused by primary surfactant deficiency and positive airway pressure. Objective: This scientific paper aims to provide nursing care to babies with Respiratory Distress Syndrome with innovative prone position interventions on oxygenation status in the perinatology room at An-Nisa Hospital, Tangerang. Method: Providing nursing care to babies with Respiratory Distress Syndrome with innovative pro-position interventions on oxygenation status. Results: Based on case studies on managed patients, the results of the interventions that have been carried out show that there is an effect of providing pronation on improving oxygenation in babies with Respiratory Distress Syndrome (RDS). Keywords: Respiratory Distress Syndrome, Prone Position